The Challenges Of SMEs In Improving Team Work Discipline Affected By Motivation And Leadership In SMES In Malang Raya - Amelia Setyawati; Feni Azadilah; Rayyan Sugangga; Adelia Rahma; Farij Ibadil Maula (International Journal of Economics and Management Research, 2023)
The situation after the COVID-19 pandemic is now challenging Indonesian MSMEs, especially in Malang Raya, to maintain the existence of the economy. Team discipline determines the success or failure of an MSME. Teamwork requires the following laws. In addition, exemplary leadership must be given as a leader. In SMEs, motivation is the encouragement that makes someone want to work to meet their needs/desires. More specifically, leaders need role models to inspire their teams. The research aims to fill in the gaps of previous studies by conducting a comprehensive study of the discipline of teamwork in MSME actors in Malang Raya which is influenced by the owner's leadership and motivation. The researchers studied conducted this research because the discipline of the UMKM team would increase the growth of UMKM. This research contributes to three things, the first is to provide insight regarding the performance team of MSME actors. Both provide valuable information for the government to increase MSME participation. The third raises the leadership mindset of Malang Raya UMKM owners. Quantitative research with explanatory research. X1 Leadership and X2 Motivation affect the dependent variable Y Work Discipline of UMKM entrepreneurs in Malang Raya. MSME actors in Malang Raya, especially restaurants that already have branches, 22 MSME owners took a census/overall sample. The indication of each variable was adapted from relevant previous research. Data collection uses a questionnaire issued by MSME owners. Data analysis used SPSS for Windows 15. The results showed that partially motivation (X1) had an effect on employee discipline. (2) Leadership (X2) has a significant effect on discipline employees. (3) Motivation (X1) and Leadership (X2) affect work discipline simultaneously. (4) Research shows that leadership has a significant effect on employee discipline.